A New Source for Schubert's Hebrew Psalm 92 (D. 953). Issue 1 (28th March 2016) - Rees, David; Schab, Alon
Abstract : In the summer of 1828, Franz Schubert composed his one and only piece in Hebrew: an excerpt of Psalm 92, set for four-part choir and Solo Baritone. The main sources available until now for this composition, a manuscript in the Gesellschaft der Musikfreunde (A-Wgm Sammlung Witteczek-Spaun Bd. 31) and a printed version in Salomon Sulzer's compendium of Viennese synagogal music, Schir Zion ( Song of Zion ), date to 1834/35 and 1839/40, respectively. A newly discovered manuscript, dating from 1832, represents an early stage in the compilation of Schir Zion and contains the earliest known source of Schubert's piece. New variant readings with regard to pitch, ornamentation and text underlay suggest that Schubert's lost autograph may not be the immediate parent of the best sources known until now. With its title in Hebrew calligraphy, moreover, this manuscript was clearly intended for Jewish use; it thus challenges the authority of Schir Zion with regard to the underlay of the Hebrew text. The manuscript demonstrates a starting point in the adaptation by later editors, including Salomon Sulzer's son Joseph, of Schubert's Hebrew composition from the living, essentially oral performance tradition of an expert cantor to the formal written requirements of publication for a far-flung audience.